Nitric oxide synthase in cardiac nerve fibers and neurons of rat and guinea pig heart. - Klimaschewski, Lars Peter; Kummer, Wolfgang; Mayer, Bernd; Couraud, Jean Yves; Preissler, Ulrike; Philippin, Bärbel; Heym, Christine (Circulation research, 1992)
Participation of nitric oxide (NO) in the autonomic innervation of rat and guinea pig hearts was investigated by applying the NADPH diaphorase technique and immunohistochemistry with NO synthase antiserum. We present evidence that NO synthase is localized in cardiac ganglion cells and nerve fibers innervating the sinuatrial and atrioventricular nodes, the myocardium, local neurons, coronary arteries, and pulmonary vessels, suggesting an involvement of NO in neurogenic heart rate regulation, myocardial cell function, neuronal transmission in cardiac ganglia, and coronary as well as pulmonary vasodilation.
Gesehen am 10.11.2025